Comparative study of the techniques to bridge the bone loss in T.K.A. - Duarte, Ricardo José de Jesus (2013)
This thesis objective was to study the biomechanical aspects of the di erent repair techniques of bone loss in the proximal tibia, in the revision of total knee arthroplasty. We sought to speci cally evaluate how each of the di erent techniques changes the load transfer to the supporting bone, thus gauging the potential for bone resorption or fatigue failure of the supporting bone. Was also assessed, in a comparative way, the stability of each repair construction of the bone defects, relatively to the solutions without bone defects. We also sought, in this work, to evaluate the e ect of the use of intramedullary stems when associated to di erent techniques. For this purpose, as a rst step, we tried to perform a detailed analysis of the knee joint in its anatomical and biomechanical aspects, with special focus on arthroplasty and its revision process. We selected the knee prosthesis P.F.C. Sigma as an element for the realization of the comparative study. The prosthetic metal elements used in the di erent bone replacement constructions were also the same model, hemi-wedge, wedge and block total. As a complement two more bone repair techniques were also compared: using only bone cement in contrast with the use of a bovine bone graft. In the following phase experimental models were developed using the tibia in composite material, where the bone defects were created and the di erent techniques applied during "in vitro" surgeries. In order to assess the changes of load transfer and stability in the region annexed to the bone defect were placed gauges, allowing the evaluation of the models main surface deformations, as well as the use of video techniques for assessing the stability of the tibial plateau in the di erent techniques. These models were subjected to a severe case of load on the medial condyle where the defect is located, proceeding to evaluation and comparison of results of deformation and stability of the bone plate. At a later stage we proceeded to the development of nite element numerical models that seek to replicate the models evaluated experimentally. The models were subjected to two load cases, one case identical to the one applied in experimental models that allowed the validation of numerical models and another load case representing a physiological load condition during the walking cycle. The numerical models have allowed the assessment of biomechanical parameters, not eligible for evaluation before, using experimental models. Thereby the strains imposed on cortical and cancellous bone in the vicinity of the defect and in the interface with this have been analysed. These same models were compared with results obtained in experimental models in order to assess their correlation. The experimental and numerical results obtained allow us to show a good correlation between these numerical models demonstrating that they are able to faithfully replicate the behaviour of experimental models. The results obtained in both types of models show changes in load transfer and stability between the di erent types of techniques. The models with full wedge and block, on average, increased the strains on the medial side (the one with defect) of the cortical bone adjacent to the implant when compared with the bone and cement graft model and metallic hemi-wedge. However is during the construction with bovine bone graft that takes place the maximum increment of strain in cortical bone, on the medial side. These increases observed in the cortical bone for larger buildings is opposite to the behavior observed in the cancellous bone at the implant interface, in which case these constructions originate a reduction of deformation on the solution without defect. So the more invasive solutions potentiate the risk of fatigue damage in cortical bone and simultaneously increase the risk of bone resorption in the adjacent cancellous bone. In terms of stability only the metallic block implant proved to be signi cantly more stable than the other techniques. The additional stability provided by stems was felt only in less invasive constructions with the use of bone cement and hemi-wedge. The experimental and numerical results obtained allow us to show a good correlation between these numerical models demonstrating that they are able to faithfully replicate the behaviour of experimental models. The results obtained in both types of models show changes in load transfer and stability between the di erent types of techniques. The models with full wedge and block, on average, increased the strains on the medial side (the one with defect) of the cortical bone adjacent to the implant when compared with the bone and cement graft model and metallic hemi-wedge. However is during the construction with bovine bone graft that takes place the maximum increment of strain in cortical bone, on the medial side. These increases observed in the cortical bone for larger buildings is opposite to the behavior observed in the cancellous bone at the implant interface, in which case these constructions originate a reduction of deformation on the solution without defect. So the more invasive solutions potentiate the risk of fatigue damage in cortical bone and simultaneously increase the risk of bone resorption in the adjacent cancellous bone. In terms of stability only the metallic block implant proved to be signi cantly more stable than the other techniques. The additional stability provided by stems was felt only in less invasive constructions with the use of bone cement and hemi-wedge.